Janie writes a play : Jane Yolen's first great story - Stemple, Heidi E. Y.; Goodnight, Madelyn (Watertown, MA : Charlesbridge, 2025)
Dissatisfied with the school play, Janie writes a new one--and grows up to be the famous author, Jane Yolen. Includes biographical note.
5-8
K-3
Keywords: Yolen, Jane -- Childhood and youth -- Juvenile fiction; Yolen, Jane -- Fiction; Authors, American -- Childhood and youth -- Juvenile fiction; Children's plays -- Juvenile fiction; Creative ability -- Juvenile fiction; Authors, American -- Fiction; Plays -- Fiction; Creative ability -- Fiction; JUVENILE NONFICTION / Biography & Autobiography / Literary; JUVENILE NONFICTION / Biography & Autobiography / Women; JUVENILE NONFICTION / Performing Arts / Theater & Musicals; Picture books; Biographical fiction